Television During Meals in the First 4 Years of Life. (June 2017) - Thimmig, Lindsay M.; Cabana, Michael D.; Bentz, Michael G.; Potocka, Katherine; Beck, Amy; Fong, Lawrence; Chao, Cewin; Caughey, Aaron B.; Wong, Angela; McKean, Michelle
The development of children's mealtime television (TV) habits has not been well studied. We assessed whether mealtime TV habits established in infancy will persist into early childhood. We analyzed data collected through parent surveys at birth and at 6-month intervals from a randomized controlled trial. We used t -tests, χ 2 tests, and a multivariable logistic regression to determine if family characteristics were associated with mealtime TV. A McNemar test was used to assess whether mealtime TV exposure changed over time. College-educated fathers and families with an annual income >$50 000 were associated with less-frequent TV exposure during children's mealtimes. It was found that 84% of children retained their level of exposure to TV during mealtimes from the first 24 months through 48 months of life. Clinicians should counsel families about mealtime TV use within the first 2 years of life because these habits seem to develop early and persist into at least early childhood.